SEKUENS TERAWETKAN TERKAIT HIV-1 - Efrida Efrida; Andani Eka Putra (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Human Immunodeficiency Virus-1 (HIV-1) have the high levels of genetic variability (molecular variation) related to the mechanismof deletions, insertions, and especially as a recombination. The recombination between subgroups and their inter subtype HIV-1 producesa new virus strain causing a certain infection. Until now there were about 40 circulating recombinant form (CRF) and 100 uniquerecombinant forms (URF) worldwide. Various HIV-1 molecular variation cause pitfalls HIV detection due to the difficulty test designed todetect all HIV-1 strains. The purpose of this study was to know the determination of the molecular variation that can identify the HIV-1genome sequences which are conserved from local isolates of West Sumatera. The method used is a descriptive study on samples of patientssuspected of being infected by HIV-1 based on the antibody screening results using rapid HIV-1 test in the laboratory of Clinical Pathologyat Dr. M. Djamil Hospital Padang. The RNA isolation and amplification by RT-PCR was performed at the Microbiology Department,Faculty of Medicine of UGM. The amplicons were sequenced using the Sanger method and analyzed by Clustal W with sequence datafrom the HIV its database. The major subtypes of HIV-1 isolates derived from local West Sumatra is AE/B with four (4) isolates (57.1%),followed by subtype AE, 2 isolates (28.6%) and B, 1 isolates (14.3%). Most of the molecular variation in this study related to thesubstitution of one base followed by deletions and insertions. The protease showed a wide variation, which consists of 20–37 substitutionsand 1–3 deletions. p24 is a highly conserved gene, followed by gp120 and vpu. Based on this study, it can be concluded that the isolatesof HIV-1 recombination is the biggest proportion with conserved region found at p24 of protein group of the gag.